Hyperglycemia-Associated Dysregulation of O-GlcNAcylation and HIF1A Reduces Anticancer Action of Metformin in Ovarian Cancer Cells (SKOV-3) - Rogalska, Aneta (Int J Mol Sci, 2018)
Although cancer cells need more glucose than normal cells to maintain energy demand, chronic hyperglycemia induces metabolic alteration that may dysregulate signaling pathways, including the O-GlcNAcylation and HIF1A (Hypoxia-inducible factor 1-alpha) pathways. Metformin was demonstrated to evoke metabolic stress and induce cancer cell death. The aim of this study was to determine the cytotoxic efficiency of metformin on SKOV-3 cells cultured in hyperglycemia and normoglycemia. To identify the potential mechanism, we assessed the expression of O-linked β-N-acetlyglucosamine transferase (OGT) and glycoside hydrolase O-GlcNAcase (OGA), as well as hypoxia-inducible factor 1-alpha (HIF1A) and glucose transporters (GLUT1, GLUT3). SKOV-3 cells were cultured in normoglycaemia (NG, 5 mM) and hyperglycemia (HG, 25 mM) with and without 10 mM metformin for 24, 48, and 72 h. The proliferation rate, apoptotic and necrotic SKOV-3 cell death were evaluated. Real-Time qPCR was employed to determine mRNA expression of OGT, OGA, GLUT1, GLUT3, and HIF1A. Metformin significantly reduced the proliferation of SKOV-3 cells under normal glucose conditions. Whereas, the efficacy of metformin to induce SKOV-3 cell death was reduced in hyperglycemia. Both hyperglycemia and metformin induced changes in the expression of genes involved in the O-GlcNAcylation status and HIF1A pathway. The obtained results suggest that dysregulation of O-GlcNAcylation, and the related HIF1A pathway, via hyperglycemia, is responsible for the decreased cytotoxic efficiency of metformin in human ovarian cancer cells.